2017
DOI: 10.1016/j.jacl.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Metreleptin therapy lowers plasma angiopoietin-like protein 3 in patients with generalized lipodystrophy

Abstract: Background Reduced triglyceride clearance due to impaired lipoprotein lipase (LPL)-mediated lipolysis contributes to severe hypertriglyceridemia in lipodystrophy. Angiopoietin-like protein 3 (ANGPTL3) and 4 (ANGPTL4) impair clearance of triglycerides by inhibiting LPL. Whether circulating ANGPTL3/4 levels are altered in lipodystrophy and the effects of leptin replacement on these ANGPTLs are unknown. Objective To examine if ANGPTL3/4 levels are elevated in patients with generalized lipodystrophy and assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Metreleptin may disrupt events that lead to lipotoxicity, as improvements in hepatic and intramyocellular lipid content, liver volume and steatohepatitis have occurred with the drug in LD patients [5,9]. Elevated levels of apolipoprotein CII and ANGPTL3 (proteins that inhibit lipoprotein lipase) in patients with LD may contribute to hypertriglyceridaemia, with levels of ANGPTL3 (but not apolipoprotein CII) being reduced by metreleptin [16,17]. Reductions in plasma levels of PCSK9 (a protein that promotes hypercholesterolaemia) have also been seen with metreleptin in LD patients, with a decline in creatinine clearance (likely indicating reduced glomerular hyperfiltration) [24].…”
Section: How Does Metreleptin Work?mentioning
confidence: 99%
“…Metreleptin may disrupt events that lead to lipotoxicity, as improvements in hepatic and intramyocellular lipid content, liver volume and steatohepatitis have occurred with the drug in LD patients [5,9]. Elevated levels of apolipoprotein CII and ANGPTL3 (proteins that inhibit lipoprotein lipase) in patients with LD may contribute to hypertriglyceridaemia, with levels of ANGPTL3 (but not apolipoprotein CII) being reduced by metreleptin [16,17]. Reductions in plasma levels of PCSK9 (a protein that promotes hypercholesterolaemia) have also been seen with metreleptin in LD patients, with a decline in creatinine clearance (likely indicating reduced glomerular hyperfiltration) [24].…”
Section: How Does Metreleptin Work?mentioning
confidence: 99%
“…Recently, Muniyappa et al [ 115 ] found that patients affected by lipodystrophy treated with metreleptin showed a marked reduction in circulating ANGPTL3 levels together with a consistent improvement in liver steatosis, whereas ANGPTL4 levels remained unchanged [ 115 ].…”
Section: Clinical Conditions Linking Angptls and Adipose Tissue Dymentioning
confidence: 99%
“…The role leptin on ANGPTL3 expression and plasma level in humans was recently documented in a study [39] conducted in patients with generalized lipodystrophy, a leptin deficient condition associated with hypertriglyceridemia [40] . These patients were found to have increased plasma levels of ANGPTL3 (but not plasma levels of ANGPTL4), suggesting the possibility that hypertriglyceridemia might be the result of ANGPTL3 mediated inhibition of LPL [39] . After metreleptin treatment, the plasma level of leptin increased whereas the plasma level of ANGPTL3 and TG showed a significant decrease [39] .…”
Section: Angptl3 and Metabolic Conditions Associated With Hypertriglymentioning
confidence: 99%
“…These patients were found to have increased plasma levels of ANGPTL3 (but not plasma levels of ANGPTL4), suggesting the possibility that hypertriglyceridemia might be the result of ANGPTL3 mediated inhibition of LPL [39] . After metreleptin treatment, the plasma level of leptin increased whereas the plasma level of ANGPTL3 and TG showed a significant decrease [39] . Thus, the finding of elevated ANGPTL3 levels in patients with lipodystrophy and their reduction following leptin treatment is consistent with the results obtained in leptin deficient mice and suggests that ANGPTL3 may contribute to hypertriglyceridemia in leptin deficient states.…”
Section: Angptl3 and Metabolic Conditions Associated With Hypertriglymentioning
confidence: 99%